Load Deflection Behaviour of Laterally Restrained TVC/GPC Slab Strips. (2015) - Naresh Reddy G.N.; Muthu K.U.
Abstract: Many factors like nonlinear material properties, cracking of concrete, creep and shrinkage of concrete are the parameters which influence the deflections of slab strips. The literature review points out that analytical methods are required to predict the entire load deflection behaviour of restrained slab strips under short term loading. A method is proposed to predict the same for Traditionally Vibrated Concrete (TVC) and Geopolymer Concrete (GPC) slabs. The results are compared with the prediction of Rankine et al and Eyre and Kemp. The results show that the proposed method is able to predict the load deflection behaviour satisfactorily of restrained TVC/GPC slab strips.